Effective Branding Strategy in Orchid Cultivation Business (Case Study on Ornamental Plants Dara Garden Karangnongko) - Ambami, Nabila Fairus Qilma; Ayu Septi Fauji , Diah (Universitas Nusantara PGRI Kediri, 2025)
Research aim :This research aims to determine the branding strategy carried out by Dara Garden and to determine how Dara Garden overcomes challenges when branding its products. Design/Method/Approach:This research uses a qualitative approach with a descriptive method. The informants in this study were the owner of Dara Garden and two employees of Dara Garden. This research was conducted through several activities, namely, pre-survey, data collection, data analysis, data presentation, and making conclusions. Data collection was carried out using observation, interviews, and documentation techniques. The data analysis technique used was data reduction. Research Findings :Based on the findings and discussion, it can be concluded that in implementing the branding strategy carried out by Dara Garden, namely carrying out promotional activities using online and offline promotional channels, strengthening the brand and product differentiation, customer service strategies that create a pleasant shopping experience, and planning a branding strategy that is effective in overcoming challenges and competition. Theoretical contribution/Originality :The results of this research contribute to branding and marketing theory, namely how to plan an effective branding strategy. Practitionel/Policy implications :Practically, this research can be adapted by similar entrepreneurs so as to increase their sales. Research limitations:The limitation of this research is that it only examines the effectiveness of the branding strategy carried out by Dara Garden..